THE STUDENTS’ SPEAKING ABILITY IN EXPRESSING GRATITUDE AND APPRECIATION - Rahmad Huda (Linguistik : Jurnal Bahasa dan Sastra, 2018)
In Indonesia, English as foreign language or second language use by most of people and English is a second language that should be mastered by language learners. In teaching English, four-language skills such as; listening, speaking, reading, and writing should be taught integrated to the language learners. Speaking is primary of language skill. The good teacher is able to find techniques in teaching and learning process. One of technique which is used in teaching speaking ability is expressing gratitude and appreciation        This study was descriptive research. The target population of this study was all of the first grade of SMK Negeri 1 Padangsidimpuan. The number of population was 400 students. The researcher took 40 students as sample. To collect the data, the researcher used speaking test. The speaking test was used to measure the students’ speaking ability and their score was analyzed by using descriptive statistic. The result of analysis indicated that the speaking skill of students was 44,45 with standard deviation (SD) was 6,32. The highest students’ score on speaking test was 76 and the lowest score was 23. It means that students’ speaking ability at the first grade of SMK Negeri 1 Padangsidimpuan was at level 2.Keywords; appreciation, gratitude, speaking ability